The evolution of Airbnb regulations - Dorine von Briel (9589481); Sara Dolnicar (10277961) (2021)
Link to open access book chapter: https://uq.pressbooks.pub/airbnb-978-1-74272-321-1/chapter/the-evolution-of-airbnb-regulations/ Chapter 4: Airbnb is a global phenomenon. Many tourism destinations, especially those with substantial and continuously growing demand, face regulatory challenges because online peer-to-peer accommodation trading platforms enable residents to make their spaces available for short-term rental. We discuss the challenges destinations and their residents face, and the regulatory responses developed to mitigate negative externalities while attempting to secure the economic benefits of Airbnb and similar platforms. Based on regulatory developments over time at some of the most affected destinations – Amsterdam, Barcelona, Berlin, Hobart, London, New York, Paris, Reykjavík, San Francisco and Tokyo – we make predictions on regulatory adjustments that may be necessary as a consequence of COVID-19.